Aid and Governance - Gisselquist, Rachel M. (Samfundsøkonomen, 2024)
The relationship between aid and governance has been a topic of considerable discussion and debate within the international development community. Good governance and effective institutions have long been spotlighted by development partners as essential for economic development and aid effectiveness. With the adoption of the Sustainable Development Goals in 2015, they have been recognized globally also as development goals in themselves – framed, as set out in SDG 16, with attention to peace, access to justice, and ‘effective, accountable, and inclusive institutions’. Yet at the same time that aid has been seen to play a pivotal role in international efforts to support and incentivize better governance, long-voiced critiques have spotlighted how it also may have (unintentionally) negative impact on the same. Recent global trends and events further have served to focus attention on the role of aid, and the challenges faced by aid, in relation to governance and institution-building.